Therapeutic applications of CRISPR-Cas9 gene editing - Bharti, Aditya; Mudge, Joann (Frontiers in Genome Editing, 2025)
CRISPR-Cas9 is a gene editing tool used extensively in biological research that is now making its way into clinical therapies. With the first CRISPR therapy obtaining approval by the United States’ Food and Drug Administration (FDA) in late 2023, we look at clinical trials of emerging therapies involving CRISPR-Cas9, currently the most prevalent CRISPR-based tool in these trials. A CRISPR-based therapy is currently approved for treatment of both sickle-cell anemia and transfusion-dependent β-thalassemia but clinical trials for CRISPR-based therapeutics include a much broader range of targets. CRISPR-Cas9 is being explored to treat cancer, infectious disease, and more. This review highlights CRISPR-Cas9 clinical trials registered at clinicaltrials.gov as of 12/31/2024.